A single centre experience with clinical use of Neria™ Guard as mode of pain and distress management in the administration of emicizumab in children - Birkedal Maj Friberg (The Journal of Haemophilia Practice)
The introduction of emicizumab as prophylactic subcutaneous (SC) administered treatment for people with haemophilia A has revolutionised its treatment and care; SC injection and the infrequent treatment intervals that can be achieved with emicizumab reduces treatment burden and interference in daily life. The efficacy and safety of emicizumab have been investigated in the Haven 1-7 trials. In contrast to the 4% of enrolled patients experiencing pain at the injection site across all seven trials, 11 out of 16 families at our treatment centre reported pain-related distress in administering emicizumab to their children, despite the application of local analgesia.